Neuroprotective effect and possible mechanism of edaravone in rat models of spinal cord injury: a systematic review and network meta-analysis - Zhou, Long-yun; Wang, Xiao-bo; Chen, Xu-qing; Li, Ran; Yu, Bin-bin; Pan, Meng-xiao; Fang, Lu; Li, Jian; Cui, Xue-jun; Yao, Min; Lu, Xiao (Frontiers in Pharmacology, 2025)
ObjectiveThe present review was developed to critically evaluate the neuroprotective effects of edaravone for experimental rat models of spinal cord injury (SCI) and generalize the possible mechanisms.MethodsSystematic searches were carried out on databases including PubMed, Embase, Web of Science, Scopus, and Cochrane Library from their inception to March 2024. Controlled studies that assessed the neurological roles of edaravone on rats following SCI were selected. The Basso, Beattie, and Bresnahan (BBB) locomotor rating scale, residual white matter area, and malondialdehyde (MDA) level of the SCI rats were systematically searched by two reviewers.ResultsTen eligible publications were included. Meta-analyses showed increased BBB scores in edaravone-treated rats compared with control ones. The effect size gradually increased from day 7 (seven studies, n = 246, weighted mean difference (WMD) = 1.96, 95% confidence interval (CI) = 1.23 to 2.68, P < 0.00001) to day 28 (seven studies, n = 222, WMD = 4.41, 95% CI = 3.19 to 5.63, P < 0.00001) after injury and then maintained stably in the following time. Meanwhile, edaravone treatment was associated with an amendment in the spared area of white matter and a lowering in the MDA expression in the lesion area. The subgroup analyses revealed that rats treated with edaravone exhibited superior locomotor recovery in compression injury models than contusion ones. In network analyses, the surface under the cumulative ranking curve gradually increased up to a dose of 5–6 mg/(kg·d) of edaravone, after which it plateaued. Mechanism analysis suggested edaravone can ameliorate oxidative stress, mitigate neuroinflammation, and counteract neuron apoptosis and ferroptosis via multiple signaling pathways to exert its neuroprotective effects.ConclusionCollectively, with a protective effect and a systematic action mechanism, edaravone warrants further investigation in SCI research and treatment. Nonetheless, in light of the limitations in the included studies, the findings in this review should be interpreted with caution.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42022374914.